Subaltern Testimony and Necropolitical Sovereignty in Shadia al-Zoubi’s Aradna al-Hurriyyah': Shahadat al-Tabi‘ wa al-Siyadah al-Nikrusiyasiyyah fi “Aradna al-Hurriyyah” li-Shadiyah al-Zu‘bi - Ahmad Fauzi Simatupang; Achmad Syafri Maulana (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2026)
This study examines Aradna al-Hurriyah by Shadia al-Zoubi from a postcolonial perspective by employing Gayatri Chakravorty Spivak's theory of Subalternity and Achille Mbembe's concept of Necropolitics. It aims to investigate the mechanisms of oppressive sovereignty in Syria and the forms of resistance articulated by subaltern subjects within testimonial literature. The study adopts a descriptive qualitative method, utilizing close reading and qualitative content analysis. The primary data consist of narratives, phrases, and linguistic expressions that represent violence, dehumanization, and freedom in the text. The findings reveal that the Syrian regime exercises internal colonialism through indiscriminate shootings, the bombing of civilian infrastructure, arbitrary detention, and the use of chemical weapons as instruments of necropolitical control. The analysis further demonstrates that testimonial narrative not only represents the lived experiences of subaltern suffering but also constitutes a space of political articulation through which silenced subjects are transformed into agents capable of renegotiating relations of power under conditions of state violence. These findings extend existing scholarship on Syrian testimonial literature by demonstrating the interconnection between subaltern experience, necropolitical governance, and the reconstruction of identity within a unified postcolonial analytical framework. Consequently, this study argues that testimonial literature functions not merely as a representation of wartime suffering but also as a medium for restoring human dignity, collective memory, and the sovereignty of identity while serving as a form of resistance to oppressive power. تتناول هذه الدراسة رواية